Unveiling the immunological landscape of disseminated tuberculosis: a single-cell transcriptome perspective - Gong, Zhen; Xu, Hongxiang; Zhang, Qiao; Wang, Guirong; Fan, Lin; Wang, Zilu; Fan, Lichao; Liu, Chang; Yu, Yanhong; Liu, Zhou; Zhou, Qiang; Xiao, Huasheng; et al. (Frontiers in Immunology, 2025)
IntroductionHematogenous disseminated tuberculosis (DTB) has an unclear etiology that likely involves multiple factors. Understanding the underlying immunological characteristics of DTB is crucial for elucidating its pathogenesis.MethodsWe conducted single-cell RNA transcriptome and T cell receptor (TCR) sequencing on samples from seven DTB patients. Additionally, we integrated and analyzed data from two published profiles of latent TB infection, three active TB cases, and two healthy controls.ResultsOur analysis revealed a significantly higher proportion of inflammatory immune cells (e.g., monocytes and macrophages) in DTB patients, along with a notably lower abundance of various lymphocytes (including T cells, B cells, and plasma cells), suggesting that lymphopenia is a prominent feature of the disease. T cell pseudotime analysis indicated a decrease in the expression of most hypervariable genes over time, pointing to T cell functional exhaustion. Furthermore, a marked absence of mucosal-associated invariant T (MAIT) cells was observed in the peripheral blood of DTB patients. In the TCR repertoire, specific polymorphisms (TRAV9-2, TRAV13-1, TRBV20-1, and TRBV5-1) and dominant clones (TRAJ49, TRBJ2-7, and TRBJ2-1) were identified. Analysis of the complementarity determining region 3 (CDR3) showed that the most frequent combination was TRAV1-2/TRAJ33, with the motif “CAAMD” being significantly reduced in DTB patients.DiscussionThese findings suggest that lymphopenia and T cell exhaustion, along with unique TCR signatures, may play critical roles in DTB pathogenesis. The reduced “CAAMD” motif and altered TCR clonotypes provide novel insights into the complex cellular dynamics associated with the disease, potentially offering new avenues for targeted immunological interventions.